EXPORT ACTIVITIES OF THE REPUBLIC OF UZBEKISTAN AND ITS REGIONS. - Abdulatifova Moxinur Alisher qizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
The task of developing a concept of regional development in the system of state and social construction in order to consistently achieve the goals of renewal and democratization of the country, the formation of civil society in Uzbekistan, and the task of radically strengthening its role and significance is, first of all, a decisive means of increasing the political and social activity of our citizens, expressing the will of the population, ensuring their direct participation in the formation of state power at the center and in localities. The process of integration of Uzbekistan into the world economy is developing rapidly, and our country’s participation in international economic organizations is an integral part of this process. Export is a factor that significantly affects this process. This article discusses the export activity and potential of Uzbekistan and the regions of Uzbekistan.